On the Content of higher technical education curricula abroad: Current Trends (Review) - O. V. Toporkova (Высшее образование в России, 2020)
Researchers consider the discrepancy between university educational programs and engineering practice to be the common problem of higher technical education today. The changes taking place at higher technical school abroad demonstrate the search for solutions of engineering education problems in developed countries. Understanding current trends in the content of higher technical education curricula in those countries will help to identify the most effective ways to solve common problems of engineering education. The article presents the results of the analysis of innovative changes taking place in the higher technical education curricula content abroad nowadays. The research materials were articles in peer-reviewed journals included in the SCOPUS database published from 2009 to 2018, proceedings of conferences held by international engineering communities. The factual basis of the study was the curricula for training engineers at a number of foreign leading universities. As a result of the research, the following innovations in the content of higher technical education curricula were identified: 1) introduction of sustainable development principles into the engineering curricula; 2) the inclusion of modules on the basics of management, entrepreneurship and innovation into the curricula, the creation of interdisciplinary programs leading to double degrees in engineering and management; 3) cooperation of universities with partner enterprises in the development of curricula; 4) the internationalization of engineering curricula, the training of future engineers for global engineering activities. The CDIO approach is considered as an innovative basis for the design of educational programs for future engineers. Those changes in the engineering curricula are aimed at bridging the gap between the contents of engineering educational programs and industrial practice, the development of competencies necessary for successful professional engineering activities, and, as a result, they contribute to improving the quality of higher technical education.